Sustainable Development and Rehabilitation of the Architectural Heritage of the Old City of Taiz (Journal of Libya for geographical studies, 2023)
The old city of Taiz represents a cultural heritage replete with its historical features, its traditional urban fabric, and its distinctive environmental pattern. the local community, and the desired economic returns decline, which made it lose its value, its heritage identity, and its tourist attractiveness. Which imposes the necessity of protecting its environment, rehabilitating its heritage, improving its urban fabric and linking it to the urban fabric of the modern city of Taiz through its sustainable development. Therefore, the study aimed to propose a vision for the sustainable development of the old city and the rehabilitation of its urban heritage, to diagnose its problems and to suggest possible mechanisms and policies that would preserve and develop the urban heritage in a way that protects its history and its environmental, urban and architectural characteristics, and employs it in tourism. To achieve the objectives of the study, a number of approaches such as descriptive analytical, inductive, historical and ecological were combined, in addition to a number of methods such as photography, cartographic representation and statistical treatment. However, the field study is the main tool for achieving the objectives of the study. The study concluded by presenting a comprehensive development vision that shows the official authorities the problems and challenges, the priorities of development, rehabilitation, protection, and ways of tourism employment in the Old City.
Keywords: Spatial features; Architectural characteristics; Current situation; Field study; Future foresight